OXA-830, a Novel Chromosomally Encoded Extended-Spectrum Class D β-Lactamase in Aeromonas simiae - Chen, Qianqian; Zhou, Wangxiao; Qian, Changrui; Shen, Kai; Zhu, Xinyi; Zhou, Danying; Sun, Zhewei; Lu, Wei; Liu, Hongmao; Li, Kewei; Xu, Teng; Bao, Qiyu; et al. (Frontiers in Microbiology, 2019)
The diversity of class D β-lactamases mediating resistance to β-lactams has been increasingly reported recently. In this study, a novel class D oxacillinase named OXA-830 was identified in a fully sequenced Aeromonas simiae strain, which was isolated from sewage discharged from a farm in southern China. OXA-830 shares the highest amino acid identity of 79.3% with an OXA-12-like variant named OXA-725. When expressed in E. coli DH5α, OXA-830 conferred resistance to penicillins and selected β-lactamase inhibitors but not to cephalosporins and carbapenems. Kinetic analysis of OXA-830 revealed a broad substrate profile including penicillins, cefazolin, cefoxitin and ceftazidime but not carbapenems. The hydrolytic activity was significantly inhibited by sulbactam, followed by tazobactam, but was less effectively inhibited by clavulanic acid. The blaOXA-830 gene was located on the A. simiae A6 chromosome and the blaOXA-830-related region was bracketed by a pair of perfect inverted repeats.